Introduction to Geography - Getis, Arthur (McGraw-Hill Higher Education, 2008)
This market-leading book introduces college students to the breadth and spatial insights of the field of geography. The authors' approach allows the major research traditions of geography to dictate the principal themes. Chapter 1 introduces students to the four organizing traditions that have emerged through the long history of geographical thought and writing: earth science, culture-environment, location, and area analysis. Each of the four parts of this book centers on one of these geographic perspectives.